ANALISIS PROTEIN DAN ASAM AMINO NATTO, MAKANAN FERMENTASI KEDELAI KUNING OLEH BASILLUS SUBTILLIS NATTO - Sahirman, Sahirman (Universitas Djuanda, 2019)
This Research aims to analyze crude protein and amino acid profile of natto from yellow soybeans from Vedca Cianjur. Protein analysis was performed using the Semi-micro Kjeldahl method, while amino acid analysis was performed using High Performance Liquid Chromatography (HPLC). Analysis of natto paste shows that natto contains an average of 22.1% crude protein and an average amino acid content of 14.46%. The results of the analysis of 15 average amino acids in Natto with HPLC showed that amino acids consist of 7 types of essential amino acids and 8 essential amino acids. The percentage of fresh weight of essential amino acids are Histidine (0.46% wb), Leucine (1.25% wb), Threonine (0.59%wb), Valine (0.81% wb), Methionine (0.13% wb), Isoleucine (0,76% wb), Fenilalanine (0.87% wb) and 8 non-essential amino acids are Serine (0.72% wb), Aspartic Acid (1.89%), Arginine (0.91%), Lysine (0.83% ), Glutamine (3.62%), Glycine (0.65%), Alanin (0.67%), and Tyrosine (0.3% wb). Glutamine is the highest level of amino acids (3.62% wb), followed by aspartic acid (1.89% wb) and Leucine (1.25% wb).